Mesenchymal Stem Cells as New Therapeutic Agents for the Treatment of Primary Biliary Cholangitis - Aleksandar Arsenijevic; C. Randall Harrell; Crissy Fellabaum; Vladislav Volarevic (Analytical Cellular Pathology)
Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease characterized by the progressive destruction of small- and medium-sized intrahepatic bile ducts with resultant cholestasis and progressive fibrosis. Ursodeoxycholic acid and obethicholic acid are the only agents approved by the US Food and Drug Administration (FDA) for the treatment of PBC. However, for patients with advanced, end-stage PBC, liver transplantation is still the most effective treatment. Accordingly, the alternative approaches, such as mesenchymal stem cell (MSC) transplantation, have been suggested as an effective alternative therapy for these patients. Due to their immunomodulatory characteristics, MSCs are considered as promising therapeutic agents for the therapy of autoimmune liver diseases, including PBC. In this review, we have summarized the therapeutic potential of MSCs for the treatment of these diseases, emphasizing molecular and cellular mechanisms responsible for MSC-based effects in an animal model of PBC and therapeutic potential observed in recently conducted clinical trials. We have also presented several outstanding problems including safety issues regarding unwanted differentiation of transplanted MSCs which limit their therapeutic use. Efficient and safe MSC-based therapy for PBC remains a challenging issue that requires continuous cooperation between clinicians, researchers, and patients.